Exercise rehabilitation programmes for pulmonary hypertension: a systematic review of intervention components and reporting quality. Issue 1 (16th October 2018) - McGregor, Gordon; Powell, Richard; Finnegan, Susanne; Nichols, Simon; Underwood, Martin
Abstract : Objectives: To identify the components, and assess the reporting quality, of exercise training interventions for people living with pulmonary hypertension. Design: Systematic review with analysis of intervention reporting quality using the Consensus on Exercise Reporting Template (CERT). Data sources: Eligible studies in the Cochrane Systematic Review of exercise-based rehabilitation for pulmonary hypertension, updated with a new search of relevant databases from 1 August 2016 to 15 January 2018. Eligibility criteria: Peer-reviewed journal articles of randomised and non-randomised controlled trials, and non-controlled prospective observational studies, investigating dynamic exercise training interventions in adult humans with diagnosed pulmonary hypertension, reporting on at least one physiological and/or psychosocial outcome. Results: Interventions typically involved cycle ergometry and walking. They were delivered as 3-week inpatient, or outpatient and/or home-based programmes, lasting for 4–15 weeks. Components relating specifically to exercise prescription were described satisfactorily and in more detail than motivational/behavioural change strategies, adherence and fidelity. Mean CERT score was 13.1 (range 8–17) out of a possible maximum score of 19. No studies fully reported every aspect of an exercise intervention to the standard recommended by CERT. Summary/conclusion: Considerable variability was evident in the components and reporting quality of interventions for exercise rehabilitation studies in pulmonary hypertension. Interventional studies using exercise training should pay greater attention to describing motivational/behavioural change strategies, adherence and fidelity. Detailed description of these parameters is essential for the safe and effective replication of exercise rehabilitation interventions for pulmonary hypertension in clinical practice. Trial registration number: CRD42018085558.